THE EFFECT OF COCONUT SHELL CHARCOAL POWDER WASTE AS A FINE AGGREGATE SUBSTITUTION IN ASPHALT CONCRETE WEARING COURSE MIXTURE - ARDIANSYAH; GALI PRIBADI; INDRIASARI (CV KULTURA DIGITAL MEDIA, 2024)
Laston, commonly known as AC (Asphalt Concrete) in Indonesia, is a type of asphalt concrete with continuous gradation designed to handle large traffic volumes. According to Waani (2013), stability is the main characteristic that makes laston a vital component. This study examines the use of coconut shell charcoal, previously considered waste, as an environmentally friendly additive. Coconut shells and rock ash are used as fillers in asphalt mixtures. It is important to test asphalt containing coconut shell charcoal to evaluate changes in its properties. The performance of asphalt mixtures, including flow, stability, VIM, VMA, Marshall Quotient, VFA, and durability values ​​are expected to increase with the addition of coconut shell charcoal. The results of the Marshall characteristic analysis of the AC-WC mixture with a filler variation of 25% substituted with coconut shell charcoal powder are 2487 kg for stability, 36.51% for VMA, 3.35 mm for flow, 26.19% for VIM, and 742 kg/mm ​​for MQ, all of which have met the specifications. However, the 2018 Bina Marga standard was not met by the VFB value of 28.27%. On the other hand, the variation of 50% coconut shell charcoal powder produced a stability value of 2568 kg, an MQ value of 756 kg/mm, a VMA value of 37.31%, a flow value of 3.4 mm, and a VIM value of 27.12%, all of which were still within the acceptable range. However, the VFB value of 27.31% did not meet the 2018 Bina Marga requirements. The findings of the mixture design presentation for cement filler are as follows: 17% for hot bin I, 45% for hot bin II, 32% for hot bin III, 6% for cement filler, and 6% for asphalt.